Investigation for Losses of M19 and Amorphous Core Materials Asynchronous Motor by Finite Elements Methods - Tarımer, İ.; Arslan, S.; Güven, M. E. (Elektronika ir Elektrotechnika, 2012)
In this study, M19 steel and amorphous material asynchronous motors have been examined by finite elements methods with v/f controlling. Performances of the motors have been investigated by means of analysis. The losses of amorphous and M19 steel core motors are compared at higher and lower frequencies. If amorphous material is used within stator core, the mass of core, and net weight of the motor would be decreased at the same motor parameters. It has been reached that the amorphous material motors would be produced lighter than M19 steel ones in the research. DOI: http://dx.doi.org/10.5755/j01.eee.18.9.2797